Human herpes virus type 8 infection : implications in Ketosis prone type 2 diabetes - (:unkn) unknown (My University, 2015)
Ketosis-Prone Diabetes (KPD) is a diabetes phenotype intermediate between type 1 and type 2 diabetes, frequently encountered in populations of African origin. This form of diabetes arouses some interest because of its clinical course marked in particular by restoring the initial impaired insulin secretion. Sobngwi et al. in 2008 established an association between HHV-8 virus and KPD in African population living in France. Nowhere else has the study been replicated. The objective of this thesis was to investigate the potential association between HHV-8 infection and KPD; then evaluate the impact of HHV-8 infection on the inflammatory profile of type 2 diabetes phenotypes. The study is based on African patients living in Africa consecutively admitted for hyperglycemic decompensation (Fasting blood glucose≥2,5g/l) at the National Obesity Centre of the Yaounde Central Hospital. More specifically, the issue was:• study the frequency of non-immune ketosis-prone diabetes (KPD);• investigate the association between HHV8 and KPD;• investigate whether HHV-8 infection is associated with an inflammatory profile that may participate in diabetes phenotypes.Was included in this study all diabetic patients old more than 18 years with acute diabetes with syndrome cardinal and ketonuria (KPD1), those who presented with an acute inaugural cardinal syndrome and diabetes ketonuria and in remission for more than three months and without ketonuria at baseline (KPD2), and those with type 2 diabetes experienced without ketonuria (T2D). Was excluded from the study all patient with stigmata of autoimmunity of type 1 A diabetes, diabetes "MODY", endocrinopathy, pancreatic disease or an autoimmune diabetes.Among all participants admitted, we collected clinical data (weight, height, BMI, waist to hip ratio, blood pressure, and the percentage of fat) and levies fasting were made (serum and peripheral blood mononuclear cells) for biological testing: glyceamia by glucose oxida
Keywords: African Research